HPB P28 Serious complications of pancreatoduodenectomy correlate with lower rates of adjuvant chemotherapy: Would selected patients benefit from neoadjuvant therapy?. (7th December 2022) - Russell, Thomas; Labib, Peter; Bowles, Matthew; Aroori, Somaiah
Abstract: Background: Pancreatoduodenectomy (PD) is recommended in fit patients with localised pancreatic ductal adenocarcinoma (PDAC) affecting the pancreatic head. Patients typically undergo PD before receiving adjuvant chemotherapy (AC). Unfortunately, up to 40% develop disease recurrence and die within a year of surgery. Recent evidence suggests that, independent of histology, severe postoperative complications are associated with a higher incidence of disease recurrence. This may be because a prolonged recovery can result in delayed or omitted AC. It could be argued that a patient who is high-risk for developing a serious complication may benefit from neoadjuvant treatment (NAT) to ensure the delivery of systemic therapy. Although delaying resection, this can treat micrometastases and down-stage tumours, increasing the likelihood of a complete resection. However, in the UK, NAT is not currently recommended in patients with resectable disease. This study aimed to compare the outcomes of PD patients who received AC to those who did not, to investigate whether serious complications were more frequent in the latter. We also aimed to investigate whether selected complications (postoperative pancreatic fistula (POPF), bile leak, post-pancreatectomy haemorrhage (PPH), delayed gastric emptying (DGE), chest infection, intra-abdominal collection and surgical site infection (SSI)) correlated with a reduced number of patients receiving AC. Methods: Patients were included if they underwent PD for histologically-confirmed PDAC at our institution between 01/09/2006 and 31/05/2015. The end date of 31/05/2015 was chosen to complete five-year follow-up for all included patients. Information on the following was collected: demographics, co-morbidities, preoperative imaging and staging, NAT (if given), preoperative blood results, procedure and intraoperative findings, postoperative management and complications, histology results, adjuvant treatment (if given), cancer recurrence, palliative treatment (if given), and five-year survival. All complications were graded using the Clavien-Dindo (CD) system. When comparing the AC group to the no AC group, medians were compared using the Mann-Whitney U test. Other outcomes were compared using Fisher's exact test. The outcomes of patients who developed the studied complications were compared to those who did not using Fisher's exact test or Student's t-test. A p-value of less than 0.05 was considered statistically significant. Statistical analyses were performed using Microsoft Excel, GraphPad Prism and IBM SPSS Statistics. Results: A total of 175 patients were included. Of the 151 who did not die within 90-days, 102 (68.5%, two patients excluded due to missing data) were commenced on AC. When patients who received AC were compared to those who did not, median survival was significantly longer in the former (688 vs 323 days, p=0.001). The two groups were similar in terms of age, gender, body mass index and American Society of Anesthesiologists (ASA) grade. Those in the AC group had less frequently experienced a postoperative chest infection (8.82% vs 34.0%, p=0.0003). The incidences of POPF, bile leak, PPH, DGE, intra-abdominal collection and SSI were similar. When the complications were combined and CD grade I complications were excluded, grade ≥II (29.4% vs 57.4%, p=0.0019) and ≥III (6.86% vs 21.3%, p=0.0233) complications were less frequent in the AC group. When patients who developed a complication were compared to those who did not, only postoperative chest infection correlated with a lower rate of AC (36.0% vs 75.0%, p=0.0003). Patients who experienced a complication which was CD grade ≥II (48.9% vs 93.1%, p=0.0099) or ≥III (29.4% vs 70.3%, p=0.0018) less frequently received AC. Conclusions: Patients who undergo PD for PDAC affecting the pancreatic head are at risk of developing serious postoperative complications which may affect their postoperative treatment. In our series, after patients who died in the perioperative period were excluded, those who developed a serious complication were less likely to receive AC. The preoperative identification of patients who are high-risk for a serious complication may have implications for management planning.